2021
DOI: 10.3390/cancers13246376
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Prognostic Effects of Aspirin in Patients Receiving Sorafenib for Hepatocellular Carcinoma: A Tale of Multiple Confounders

Abstract: Case–control observational studies suggested that aspirin might prevent hepatocellular carcinoma (HCC) in high-risk patients, even if randomized clinical trials are lacking. Information regarding aspirin in subjects who already developed HCC, especially in its advanced stage, are scarce. While aspirin might be a low-cost option to improve the prognosis, multiple confounders and safety concerns are to be considered. In our retrospective analyses of a prospective dataset (n = 699), after assessing the factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Aspirin use was reported in association with better clinical outcomes and survival benefits in patients who received sorafenib treatment for HCC. 36 As to our patients, none of sorafenib-responders had used aspirin during the sorafenib or subsequent therapies for HCC. Therefore, we did not include aspirin use in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin use was reported in association with better clinical outcomes and survival benefits in patients who received sorafenib treatment for HCC. 36 As to our patients, none of sorafenib-responders had used aspirin during the sorafenib or subsequent therapies for HCC. Therefore, we did not include aspirin use in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that aspirin, a low-cost medication for cardiovascular protection, was associated with reduced incidence of and lower mortality from HCC in patients with viral hepatitis infection [28]. Ielasi et al also reported recently that aspirin use could improve survival in HCC patients who received sorafenib treatment [29]. Statins could also benefit patients with reduced risk of recurrence and improved survival after a surgical resection or liver transplant [30].…”
Section: Discussionmentioning
confidence: 99%
“…34 Chronic use of low-dose aspirin has been recently advocated as a positive predictive factor in sorafenib-treated patients. 21,22 Its extensive use in LT patients to prevent the occlusion of the hepatic artery anastomosis 34 could be another factor contributing to the OS values. Second, the preserved liver function and good performance status allowed a more frequent use of combined locoregional treatments during and Copyright © 2022 Wolters Kluwer Health, Inc.…”
Section: Discussionmentioning
confidence: 99%